2022
DOI: 10.1021/acs.analchem.2c00854
|View full text |Cite
|
Sign up to set email alerts
|

Mass-Encoded Suspension Array for Multiplex Detection of Matrix Metalloproteinase Activities

Abstract: This work designed a mass spectrometric biosensing strategy for the multiplex detection of matrix metalloproteinases (MMPs) with a mass-encoded suspension array. This array was fabricated as multiplex sensing probes by functionalizing magnetic beads with MMP-specific peptide-isobaric tags for relative and absolute quantification (iTRAQ) conjugates, which contained a hexahistidine tag for surface binding, a substrate region for MMP cleavage, and a coding region for the specific MMP. The integration of the multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…Therefore, sensitive detection of MMP-2 is of great necessity in early disease diagnosis and therapy. Recently, some analytical technologies like mass spectrometry, 4 electrochemistry, 5 and Raman spectroscopy 6 have been applied in protein detection. However, the above testing methods exhibited certain shortcomings of low sensitivity, complex operation and expensive equipment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, sensitive detection of MMP-2 is of great necessity in early disease diagnosis and therapy. Recently, some analytical technologies like mass spectrometry, 4 electrochemistry, 5 and Raman spectroscopy 6 have been applied in protein detection. However, the above testing methods exhibited certain shortcomings of low sensitivity, complex operation and expensive equipment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In another example, Hu et al reported the development of a mass spectrometric biosensing strategy for multiplex detection the activity of MMP-2 and MMP-7 (Figure 13b). [86] The sensor was developed by coating the nickel-nitrilotriacetic acid-modified magnetic beads (Ni-NTA MBs) with MMP-specific peptideisobaric tags for relative and absolute quantification (iTRAQ) conjugates through the specific binding between Ni-NTA and hexahistidine tag. In this sensor, the iTRAQ 114 and iTRAQ 117 were used for MMP-2 and MMP-7 detection, respectively, and iTRAQ 115 served as the control.…”
Section: Ms Sensorsmentioning
confidence: 99%
“…Reproduced with permission. [ 86 ] Copyright 2022, American Chemical Society. c) An MRI sensor MMP‐Fe/IONPs for MMP‐2 detection.…”
Section: Enzymatic Activity‐based Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to overcome the bottleneck for multiplex enzyme activity assays, our group proposed “mass spectrometric biosensing” as a powerful tool for multiplex analysis with mass-tag probes, which could transfer the target information to explicit mass spectrometric signals . This idea was successfully applied to the detection of MMP activities with a mass-encoded suspension array by ultrahigh performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS) . The proposed method made use of the relative decrease of peak area ratios of coding regions to detection target MMP-2 and MMP-7 activities.…”
Section: Introductionmentioning
confidence: 99%